Evaluation of corrosion and wear behaviour of nickel tungsten carbide electrodeposited with different tungsten carbide concentration and current density - Kamdi, Zakiah; Badarulzaman, Nur Azam; Sukkeri, Muhammad Adeeb Reezan; Hassan, Muhammad Syafiq; Mohamed Hatta, Mohamed Nasrul; Ainuddin, Ainun Rahmahwati (UTHM, 2018)
Cermets (ceramic-metal) materials have been popular for wear and corrosion application due to their ability to withstand both conditions. In current work, cermets tungsten carbide-nickel (WC-Ni) composite coating has been deposited using direct current (DC) electrodeposition in Watt’s bath on mild steel. The current density were varied at 0.08 Acm-2 , 0.14 Acm-2 and 0.20 Acm-2 while others parameter i.e. bath temperature and stirring rate were remain constant. Three carbide concentrations were used that are 15 g/l, 20 g/l and 25g/l. This work is focusing on determining the effect of current density and carbide concentration to the wear and corrosion behaviour of WC-Ni cermet coating. The surface morphology, microstructure and elemental composition were analysed using scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS). The wear and corrosion behaviour were evaluated using weight loss methods and three electrode electrochemical tests respectively. The abrasive wear was done against 800 grit silicon carbide paper. While for corrosion test, two types of electrolytes that were used are 0.5 M sulphuric acid and 3g/l sodium chloride at room temperature. The micro-hardness of the coating was analysed using Vickers micro-hardness tester with 100g load. It is found that, the wear resistance increases with increasing of carbide content and current density. The corrosion resistance was also increase with increasing of carbide content. For current density, it is slightly decrease of corrosion resistance after deposition at 0.20 Acm-2 due to uneven distribution of carbide. The hardness of the cermet coatings were increase with increasing of carbide content and current density. It can be concluded that with 25g/l carbide and at 0.14 Acm-2 current density shows the optimum combination to achieve high wear and corrosion resistance.